Pengaruh Posisi High fowler 900 Terhadap Stabilitas Hemodinamik Pada Pasien Gagal Jantung Kongestif di Ruang Cardiovascular Care Unit (CVCU) - Pipin Yunus; Susanti Monoarfa; Febriyanti Lamusu (Jurnal Keperawatan Florence Nightingale, 2026)
Patients with congestive heart failure often experience hemodynamic stability disorders due to the prognosis of their disease, so that non-pharmacological treatment is needed, one of which is the provision of a therapeutic high fowler 900 position. The purpose of this study was to determine the Effect of High Fowler 900 Position on Hemodynamic Stability in Congestive Heart Failure Patients in the Cardiovascular Care Unit (CVCU). The research design used a quantitative pre-experimental design with a pre-post test design, involving 19 respondents using accidental sampling. Research Results: The results of the study using the non-parametric Wilcoxon signed rank test showed that there was an Effect of High Fowler 900 Position on Hemodynamic Stability in Congestive Heart Failure Patients in the CVCU Room of Prof. Dr. Soetomo Hospital. H. Aloei Saboe is proven by p. value (<0.05). Conclusion: High fowler 900 position is effective in improving hemodynamic stability in heart failure patients and can be used as a non-pharmacological nursing intervention that is easy to apply